Program Edukasi Cyber Crime pada Siswa SD Negeri 35 Kota Sorong - Melda Agnes Manuhutu; Evelyna Evelyna; Ferderika Ferderika; Fanessa Fanessa; Gracella Gracella; Kailla Kailla; Risner Risner; Revan Revan; Monalia Monalia; Alfares Alfares (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of information technology poses the threat of Cybercrime, especially phishing, which is increasingly targeting students. Initial observations at SD Negeri 35 Sorong City show that most students of class 6C do not understand phishing and the dangers it causes. This community service activity aims to increase students' understanding of Cyber crime, especially phishing techniques, through an interactive and practical approach. The implementation method consists of four stages, namely preparation, socialization, interactive training, and mentoring and evaluation, involving 24 students of class 6C. The results showed a significant improvement in students' ability to recognize phishing characteristics, distinguish between real and fake links, and understand digital account protection measures. The simulation method and live URL analysis have proven to be effective in increasing student active engagement. In addition, this activity has a positive impact in the form of increasing digital literacy and forming safe internet habits among elementary school students. Thus, this program can be a relevant educational model to strengthen Cybersecurity culture from an early age, while supporting the creation of a younger generation that is smarter and more vigilant against digital threats.